2019
DOI: 10.9734/jenrr/2019/v2i229734
|View full text |Cite
|
Sign up to set email alerts
|

Wind Energy Potential Assessment of Great Cumbrae Island Using Weibull Distribution Function

Abstract: Wind energy is among the fastest growing energy generation technology which is highly preferred alternative to conventional sources of energy. The major Scottish Government target is to deliver 30% of her energy demand by 2020 from renewable sources of energy as well as meeting the emission targets as set under the Scotland Climate Change Act 2009. In this paper, wind energy potential assessment of Great Cumbrae Island was investigated. For this, a ten year mean monthly wind speed at height 50 m obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…One of the main outcomes of this study was to identify a potential future offshore wind farm site with an annual power production capacity of approximately 35.36 MWh. Emmanuel et al [8] determined the wind farm construction feasibility at the Great Cumbrae Island near the coast of Ayrshire in the United Kingdom (UK). They used wind data measured over ten years at 50 m in height.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main outcomes of this study was to identify a potential future offshore wind farm site with an annual power production capacity of approximately 35.36 MWh. Emmanuel et al [8] determined the wind farm construction feasibility at the Great Cumbrae Island near the coast of Ayrshire in the United Kingdom (UK). They used wind data measured over ten years at 50 m in height.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mohammadi et al 2016 [22], it was found that different sites used different methods of Weibull parameter estimation since the wind characteristics of the site determine that best approximation method. Kombe et al [16] used the Weibull distribution function to fit 10 years of monthly mean wind speed data of Great Cumbrae Island. The calculated mean wind speed was 7.598 m/s and the wind power density calculated for the region was 483.50 W/m 2 .…”
Section: Introductionmentioning
confidence: 99%